Development of Some Organs Derived from the Three Embryonic Germ Layer in a Degus Ectopic Pregnancy and Presence of a Cytotrophoblast That Mimics Human Chorionic Placenta. (16th July 2014) - Bosco, C.; Díaz, E.; González, J.; Gutierrez, R.
Abstract : This report describes a case of abdominal pregnancy in an adult female degu from which we recovered two large tissular masses from the peritoneal cavity. The bigger one showed a number of thin vascular connections to the serosa layer of the small intestine. It was also directly connected to the smaller mass by a thin membranous process. The surface of the bigger mass facing the small intestine wall showed the presence of chorionic villous that resembled a villous human chorionic placenta, rather than the hemomonochorial labyrinthine placenta, characteristic of this species. This unusual finding leads us to postulate that in the degu's uterus the cytotrophoblast is exposed to a number of factors that will activate cascades of cellular and molecular events that ultimately will be signaling the cytotrophoblast to develop into a labyrinthine hemomonochorial placenta. In absence of the proper uterine environment, as is the case of the abdominal pregnancy in the peritoneal cavity reported here, the lack of signaling will lead the cytotrophoblast to develop into a villous chorionic placenta, similar to that observed in human.